2018
DOI: 10.1016/j.ttbdis.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Combining public participatory surveillance and occupancy modelling to predict the distributional response of Ixodes scapularis to climate change

Abstract: Ixodes scapularis, a known vector of Borrelia burgdorferi sensu stricto (Bbss), is undergoing range expansion in many parts of Canada. The province of New Brunswick, which borders jurisdictions with established populations of I. scapularis, constitutes a range expansion zone for this species. To better understand the current and potential future distribution of this tick under climate change projections, this study applied occupancy modelling to distributional records of adult ticks that successfully overwinte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 71 publications
0
27
0
4
Order By: Relevance
“…About 300,000 new cases are diagnosed in the United States annually (3,4). Tick-borne infections are on the rise in the USA and Europe due to a host of different factors including climate change (5,6) and disruption of predator density in suburban areas (7). Recent studies on tick prevalence and pathogen load have identified new geographical areas where vector ticks are present (8), as well as novel tick-borne pathogens present in areas where they had not previously been identified (such as B. miyamotoi in Northern California) (9).…”
Section: Introductionmentioning
confidence: 99%
“…About 300,000 new cases are diagnosed in the United States annually (3,4). Tick-borne infections are on the rise in the USA and Europe due to a host of different factors including climate change (5,6) and disruption of predator density in suburban areas (7). Recent studies on tick prevalence and pathogen load have identified new geographical areas where vector ticks are present (8), as well as novel tick-borne pathogens present in areas where they had not previously been identified (such as B. miyamotoi in Northern California) (9).…”
Section: Introductionmentioning
confidence: 99%
“…About 300,000 new cases are reported in the United States annually (3, 4). Tick-borne infections are on the rise in the USA and Europe due to a host of different factors including climate change (57), and disruption of predator density in suburban areas (8). Recent studies on tick prevalence and pathogen load have identified new geographical areas where vector ticks are present (9), as well as novel tick-borne pathogens present in areas where they had not previously been identified (such as B. miyamotoi in Northern California)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the inaccuracy of serological testing fuels the debate over chronic Lyme disease, as most physicians claim the infection does not persist after short-term antibiotics while patients and patient advocates counter that serological tests are simply inadequate at detecting the infection. The challenge is in how to move forward, especially in relation to public policy [30,31].…”
Section: Introductionmentioning
confidence: 99%